(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Among the structural elements that create the conditions for the sustainable development of the tourism sector and the stability of various branches of activity, the general infrastructure includes electricity and housing communications, roads, drinking water supply, various financial and economic organizations, insurance companies, and organizations. They are used as resources in the tourism sector, but without these resources, the tourism sector will not develop sufficiently.